Structure and biogeochemical process of microaggregates in a water source area of China’s South-to-North Water Diversion Project according to different land use types - Li, Chunjie; Guo, Shili; Shang, Songhao; Qi, Pengcheng; Li, Bailian (Frontiers in Environmental Science, 2023)
Soil biogeochemical processes have the potential to impact water quality in source areas of water diversion projects. This study aimed to explore the differences in biochemical processes and mechanisms at the microaggregate scale for different land use types in the water source area of China's Middle Route of the South-to-North Water Diversion Project. The study compared four typical land use types—forests, shrublands, terraces, and cultivated land—by characterizing the microaggregates using various analytical techniques, including scanning electron microscopy (SEM), SEM-EDS plane scan analysis, X-ray diffraction (XRD), X-ray fluorescence (XRF) spectroscopy, and Fourier transform infrared (FTIR) spectroscopy. Microaggregates from forests and shrublands had a flocculent spatial structure, while those from terraces had a nondirectional plate-like spatial structure, and those from cultivated land had a laminar spatial structure. Additionally, elements such as Mg, Al, and Fe were enriched in clay particles when combined with microaggregates. The mineral composition of clay varied significantly between different land use practices, with illite, chlorite, anorthite, albite, and quartz present in higher proportions in terraces and cultivated land than in forests and shrublands. Moreover, the contents of transitional elements such as Ti, Fe, Zn, Y, and Zr increased with each successive land use practice. Soil organic matter (SOM) was observed to decline in the order of forest > shrubland > terraces > cultivated land. Over-tillage appeared to be the primary mechanism of organic matter loss due to long-term tillage. The results of this study provide valuable insights into soil erosion and chemical transport dynamics. The mineral composition and spatial structure of microaggregates are important determinants of soil biochemical processes and mechanisms, which can influence water quality. The findings suggest that forest and shrubland management practices may be more conducive to maintaining soil health and water quality in source areas of water diversion projects.